NILAI ESTETIKA DAN PERAN TARI TIRIK LALAN DALAM KEBUDAYAAN KALIMANTAN SELATAN - Firda Syahtari, Adinda; Juniati Siman, Nadia (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
The Tirik Lalan dance, originating from the Pandahan area of Tapin Regency, is an entertainment dance that depicts the romantic interaction between a man and a woman. This study aims to explore the aesthetic values of the dance in terms of visual, kinetic, and symbolic aspects. Additionally, this journal highlights the important role of the Tirik Lalan dance in preserving and developing the culture of South Kalimantan. This dance serves not only as a means of entertainment but also as a medium to strengthen community identity and pass on traditional values to future generations. A deeper understanding of the aesthetic values and social roles of the Tirik Lalan dance is expected to contribute to the preservation of cultural heritage and enhance appreciation for the local cultural richness of South Kalimantan.